The Strategic Measures for the Industrial Security of Small and Medium Business - Chang-Moo Lee (The Scientific World Journal)
The competitiveness of companies increasingly depends upon whether they possess the cutting-edge or core technology. The technology should be protected from industrial espionage or leakage. A special attention needs to be given to SMB (small and medium business), furthermore, because SMB occupies most of the companies but has serious problems in terms of industrial security. The technology leakages of SMB would account for more than 2/3 of total leakages during last five years. The purpose of this study is, therefore, to analyze the problems of SMB in terms of industrial security and suggest the strategic solutions for SMB in South Korea. The low security awareness and financial difficulties, however, make it difficult for SMB to build the effective security management system which would protect the company from industrial espionage and leakage of its technology. The growing dependence of SMB on network such as internet, in addition, puts the SMB at risk of leaking its technology through hacking or similar ways. It requires new measures to confront and control such a risk. Online security control services and technology deposit system are suggested for such measures.